Report of a New Mammalian Tapeworm Moniezia govindae - M. N. Kadam2, Nitin Padwal1*, (Recent Research in Science and Technology, 2011)
The present communication deals with the report of a new mammalian tapeworm Moniezia (B) govindae n.sp. from Capra hircus (L) from Gangapur Dist. Aurangabad (M.S.). It comes closer to all the known species of the genus Moniezia [2] but differs from some characters like globular scolex, long neck, mature proglottids broder than long, testes 100-140 in numbers, cirrus pouch oval in shape. Ovary nut shaped, vagina posterior to cirrus pouch and vitelline gland post ovarian.